Epilepsy in Juvenile Neuronal Ceroid Lipofuscinosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The clinical characteristics of epilepsy and optimal antiepileptic drug therapy were surveyed in 60 patients (mean age 16 years, range 5-33) with juvenile neuronal ceroid lipofuscinosis (JNCL), followed at the University of Helsinki, Finland.